Personalistic Christology of Czeslaw Stanislaw Bartnik - Gorban, Richard (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2017)
In this article, the author gives analysis of peculiarities of the Personalistic Christology, advocated by Czeslaw Stanislaw Bartnik, a Polish Catholic philosopher and theologian, who believes that the doctrine about Jesus Christ is not a complete and finally settled system, but a theological theory that is always open for deeper study. Thus, he interprets it in the philosophical sense, from the perspective of modern Personalism. The author proves that a Polish thinker considers the Personality of Christ a particular God’s subsistence, the fullness of existence of which can only be revealed through the personality category, since the sole way to understand the synthesis of a human and God’s nature, as a result of fusion in the personality of Christ, is possible through personal relations-bonds of the Trinitarian character (relatio), due to which one sentient combines into a single entity two different natures: divine and human. The author marks that, according to Czeslaw Bartnik, it is the phenomenon of a personality that best explains the essence of Jesus Christ, his nature, being and structure. That is why a personalistic approach in Christology is one of the most fruitful ones within the context of modern anthropologic refocusing of Christian Theology that was declared at the Second Vatican Conference as the most significant task of the course of Catholic renewal (aggiornamento).